Late correction of tetralogy of Fallot in children (Swiss Medical Weekly, 2019)
AIM OF STUDY To report our experience of late correction after infancy in patients with tetralogy of Fallot (ToF). METHODS Observational single-centre retrospective analysis of the surgical techniques and perioperative development of patients from developing countries undergoing total surgical correction of ToF after infancy, between 1 November 2011 and 30 November 2016. Variables are presented as numbers with percentages or as mean ± standard deviation. Due to the setting of the humanitarian programme, clinical and echocardiographic follow-up procedures could be conducted for only one month postoperatively. RESULTS Twenty-five children (mean age: 70.8 ± 42 months, range 23-163; 44% female) underwent total surgical correction of ToF. Two patients (0.8%) initially received a Blalock-Taussig shunt and underwent subsequent correction 24 and 108 months later, respectively. Preoperative mean right ventricular/pulmonary artery (RV/PA) gradient was 84 ± 32 mm Hg, with a Nakata index of 164 ± 71 mm2/m2. Major aortopulmonary collateral arteries (MAPCAs) were observed in eight children (32%), six (26%) of whom underwent transcatheter closure before surgery. 24 children (96%) underwent a valve-sparing pulmonary valve repair and one patient received a transannular patch (TAP). There were no cases which saw major adverse cardiac and cerebrovascular events (MACCE). Mean duration of mechanical ventilation was 28 ± 19.6 hours (range 7-76). Pre-discharge echocardiography demonstrated a mean RV/PA gradient of 25 ± 5.7 mm Hg, with left ventricular ejection fraction >60% in all cases. Overall length of hospital stay was 11.7 ± 4.5 days. There were no in-hospital mortality cases. CONCLUSIONS Late surgical correction of ToF can be safely performed and produce highly satisfying early postoperative results comparable to those of classical “timely” correction. A valve-sparing technique can be applied in the majority of children.